A statistically adaptive sampling policy to the Hotelling's T2 control chart: Markov chain approach. Issue 13 (2nd July 2016) - Seif, Asghar; Faraz, Alireza; Saniga, Erwin; Heuchenne, Cédric
ABSTRACT: We present an alternative sampling scheme for the Hotelling's T 2 control chart with variable parameters (VP T 2 ) which allows the sampling interval h, the sample size n, and control limit k to vary between minimum and maximum values while keeping the warning line fixed over time. Our method uses only one measurement scale to overcome the difficulties of using two scales in practice. Later, we demonstrate the merits of the method in terms of its performance in detecting small-to-moderate shifts and its ease of application.